Preset-based generation and exploration of visualization designs. (December 2015) - Schulz, Hans-Jörg; Hadlak, Steffen
Abstract: Generating the "right" visual representation for the data and task at hand remains a standing challenge in visualization research and practice. A variety of different approaches to produce visual representations have been proposed in the past, including such noteworthy instances as visualization by example and visualization by analogy . With this paper, we add a new twist to creating visual representations by proposing a way to construct new visualization designs by blending together a number of existing visual representations, called presets . We embed this novel blending approach in suitable visual interfaces, such as a gridded canvas to be used by the casual user in the style of a palette for mixing colors, or a range of sliders to be used by the expert user in the style of a studio mixer for audio tracks. These can be employed for rapid prototyping of a specific visual representation, as well as to explore the overall design space of visual representations captured by our approach. We showcase our preset-based blending and its interfaces with examples of the design of 2D tree visualizations and product plots. Abstract : Graphical abstract: Abstract : Highlights: A novel way to describe visualizations as a set of numerical configuration parameters. Two new interfaces that use these parameters to blend visualizations into new ones. Examples from the fields of tree visualization and product plots utilizing both.